Hiddenness and alterity : philosophical and literary sightings of the unseen - Mensch, James Richard (Duquesne University Press, 2005)
"Using resources of phenomenology to examine how we are able to engage in self-concealment, Mensch presents a unified theory of the role of the other in our relations to the world" -- Provided by publisher.
Keywords: Self (Philosophy); Other (Philosophy); Phenomenology; Ethics; identiteetti; itse; toiseus; fenomenologia; etiikka; identitet (självbild); självet; främmandeskap; fenomenologi; etik